Minat Mahasiswa terhadap Bahasa Arab: Studi pada Program Pendidikan Ulama Tarjih FakultasAgama Islam Universitas Muhammadiyah Malang - Fathor Rahim (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2019)
This article explains about the interest of students Program Pendidikan Ulama Tarjih University of Muhammadiyah Malang (PPUT UMM) towards Arabic language education program. The study of the interests of prospective ulama students in Muhammadiyah is important, because: First, it has never been done, especially relating specifically to improving the ability of Arabic as a "science tool"; Secondly, it is very useful to identify the quality of knowledge of the tools of the Muhammadiyah ulama candidates; third, the quality of the tool knowledge possessed is certainly useful as a recommendation for lecturers supporting Islamic sciences. The study uses an elaborative research model, namely qualitative, quantitative and descriptive. This article argues, PPUT students have a strong interest in pursuing Arabic.